Housing Affordability and Livability in Baghdad: A Spatial Analysis of Supply–Demand Mismatch (Architecture Image Studies, 2026)
This study investigates the incongruity between housing supply and demand in Baghdad, Iraq, using a combined-methods framework that synthesizes affordability, spatial distribution, and service sufficiency. The study integrates quantitative data from online surveys, qualitative perspectives from GIS-based spatial analysis of residential complexes, and People's opinions from discussions on social media. To outline a more thorough assessment, the study puts forward a composite suitability indicator that evaluates the dual aspects of affordability and, using price classes as a proxy for purchasing power, the adequacy of basic services, measured by a service-availability score (0–5) for schools, mosques, health centers, markets, and green spaces. Projects are classified into three suitability levels—highly suitable, suitable, and not suitable—based on these combined criteria. The findings show a structural imbalance in Baghdad’s housing market, with most supply concentrated in high-priced categories and few projects meeting the demand of middle- and low-income households. The spatial analysis shows that attention remains focused on the city’s core, while outlying areas receive limited, lower-quality services. The study also points out that high-rise residential buildings are common, though they often don’t match residents' preferences—many prefer more adaptable homes that are spread out horizontally. These economic, service-related, and spatial mismatches increase housing exclusion and weaken social equity and urban quality of life. The study concludes by offering policy recommendations to encourage affordable housing through incentives, promote planning that integrates services into projects on the city’s outskirts, and support adaptable designs that align with local culture. These steps aim to help make urban development fairer to all.